Fabrication of biomimetic patterned PCL membranes mimicking the complexity of rubus fruticosus leaves surface - Monteiro, N. O. (2021)
The development of bioresponsive interfaces that can induce a beneficial impact on cell mechanisms, such as adhesion, proliferation, migration and differentiation are of utmost relevance in Tissue engineering (TE) approaches. The surface topography is a captivating property that contribute to interesting cell responses, being inspired by several cues found in nature. Therefore, the study herein presented reports the fabrication of a surface topography using theÂ Rubus fruticosusÂ leaf on spin casting polycaprolactone (PCL) membranes. The topography was replicated by replica molding rapid fabrication technique and nanoimprint lithography (NIL). The biomimetic patterned PCL membranes (bpM) were successfully produced revealing high detail due to the complexity of the leafâ s surface ranging from the stroma structures to nerves structures. The thermal evaluation revealed a slight increase of crystallinity of the bpM compared with the other tested conditions. However, did not induce significant effects on the melting and recrystallization temperatures. The mechanical properties revealed that the young modulus increase from 3.2 MPa to 4.4 MPa during the imprinting process. However, bpM presents a lowest elongation capacity than bare membrane (bM) (1076 to 444 %, respectively) due to the heterogeneous thickness induced by the topography. The selected topography revealed to promote a positive bioresponse, depicted by the improvement of the cellular behaviour and different organization. This promising strategy revealed that circumventing the traditional topographies by nature mimetic topographies is fundamental for the development of innovative bioresponsive substrates that can tune cellular behaviour in TE strategies.